2017 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Despite strong economic growth in 2017, antiglobalization sentiments increased uncertainty about inter-national cooperation. A rise in hunger, linked with conflict and climate shocks, reconfirmed the importance of IFPRI’s mission-providing research-based policy solutions that reduce poverty and end hunger and malnutrition sustainably-and the need for greater global efforts to improve our food systems and accelerate progress toward ending hunger. With its refreshed strategy, IFPRI is proud to contribute to progress toward achieving the Sustainable Development Goals.